OC-032 Outcome on home parenteral nutrition: 33 years experience from a national centre. (28th May 2012) - Dibb, M; Carlson, G; Bradley, A; Anderson, I; Shaffer, J; Teubner, A; Lal, S
Abstract : Introduction: Home parenteral nutrition (HPN) is an essential treatment modality for patients with Type 3 intestinal failure (IF), but long term data on the factors associated with HPN dependence and survival are limited. Methods: Medical records of patients with IF who received HPN for more than 3 months from a national IF Unit between 1978 and 2011 were reviewed. Kaplan–Meier curves and Cox regression analysis were performed to identify factors associated with HPN dependence and poor prognosis. Results: Case notes of 547 patients were reviewed. The overall probability of survival was 89%, 67%, 58% and 27% at 1, 5, 10 and 20 years after starting treatment. Multivariate analysis demonstrated an association between diagnosis and survival; Crohn's disease, mesenteric ischaemia and pseudo-obstruction were associated with a better outcome. There was also an association with increasing age at IF diagnosis and poor outcome. There was no association between small bowel length or the occurrence of catheter-related infection and survival. 14.7% (25/170) of deaths were related to HPN complications. Line sepsis and IF-associated liver disease were considered to be the cause of death in 10 and 15 patients respectively (mean survival of these patients: 67 months (range 6–223); 32% within the first 2 years of treatment). Continued HPN dependence in survivors was 83%, 63%, 59% and 53% at 1, 5, 10 and 15 years respectively. 80% of those who achieved nutritional independence from HPN did so within the first 7 years of treatment. Surgical reconstruction resulted in a shorter period of HPN dependence than adaptation and/or medical therapies (19.8 vs 32.8 months respectively) p=0.008. On multivariate analysis, mechanism of IF was significantly associated with the likelihood of HPN independence: patients with gastro-intestinal dysmotility or malabsorption were less likely to achieve HPN independence, whereas those with short bowel syndrome with or without enterocutaneous fistula were more likely achieve HPN independence. Of the latter group, patients with a small bowel length >150 cm were 3.5× more likely to achieve nutritional independence compared to those with <50 cm. Conclusion: This is the largest reported long-term experience of survival and dependence on HPN and will inform future decisions about evolving alternative therapies for type 3 IF, such as small bowel transplantation and lengthening. Nutritional autonomy can be achieved in a significant proportion of patients through adaptation, medical treatment of underlying disease and/or surgical reconstruction. Competing interests: None declared.